Development Of Floor Gymnastic Learning Device Based On Articulate Storyline Application - Sigit Wahyudin; Lokananta Teguh Hari Wiguno; Ari Wibowo Kurniawan (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
In conducting research, it certainly has a specific goal, namely to develop a teaching and learning tool for floor gymnastics material based on the articulate storyline application. The method used when conducting research is the Research and Development (R&D) approach with the development model that has been carried out. Assessments from several experts including learning experts obtained good results, and for the media expert's assessment obtained a good value, the SD game expert's assessment obtained a good value, the PJOK expert's assessment obtained a good value, the floor gymnastics expert's assessment obtained a good value, and when conducting small group trials and large group trials get very good ratings and can be used by educators to teach floor exercise material. So it can be concluded that the product development of floor exercise learning tools based on the articulate storyline application can be used for teaching & can be used as a reference for learning success for PJOK material for class IV Elementary School when learning floor gymnastics.